Janus-kinase-2 relates directly to portal hypertension and to complications in rodent and human cirrhosis. Issue 1 (17th September 2015) - Klein, Sabine; Rick, Johanna; Lehmann, Jennifer; Schierwagen, Robert; Schierwagen, Irela Gretchen; Verbeke, Len; Hittatiya, Kanishka; Uschner, Frank Erhard; Manekeller, Steffen; Strassburg, Christian P; Wagner, Kay-Uwe; Sayeski, Peter P; et al.
Abstract : Objective: Angiotensin II (AngII) activates via angiotensin-II-type-I receptor (AT1R) Janus-kinase-2 (JAK2)/Arhgef1 pathway and subsequently RHOA/Rho-kinase (ROCK), which induces experimental and probably human liver fibrosis. This study investigated the relationship of JAK2 to experimental and human portal hypertension. Design: The mRNA and protein levels of JAK2/ARHGEF1 signalling components were analysed in 49 human liver samples and correlated with clinical parameters of portal hypertension in these patients. Correspondingly, liver fibrosis (bile duct ligation (BDL), carbon tetrachloride (CCl4 )) was induced in floxed- Jak2 knock-out mice with SM22-promotor (SM22 Cre+ - Jak2 f/f ). Transcription and contraction of primary myofibroblasts from healthy and fibrotic mice and rats were analysed. In two different cirrhosis models (BDL, CCl4 ) in rats, the acute haemodynamic effect of the JAK2 inhibitor AG490 was assessed using microsphere technique and isolated liver perfusion experiments. Results: Hepatic transcription of JAK2/ARHGEF1 pathway components was upregulated in liver cirrhosis dependent on aetiology, severity and complications of human liver cirrhosis (Model for End-stage Liver disease (MELD) score, Child score as well as ascites, high-risk varices, spontaneous bacterial peritonitis). SM22 Cre+ - Jak2 f/f mice lacking Jak2 developed less fibrosis and lower portal pressure (PP) than SM22 Cre− - Jak2 f/f upon fibrosis induction. Myofibroblasts from SM22 Cre+ - Jak2 f/f mice expressed less collagen and profibrotic markers upon activation. AG490 relaxed activated hepatic stellate cells in vitro. In cirrhotic rats, AG490 decreased hepatic vascular resistance and consequently the PP in vivo and in situ. Conclusions: Hepatic JAK2/ARHGEF1/ROCK expression is associated with portal hypertension and decompensation in human cirrhosis. The deletion of Jak2 in myofibroblasts attenuated experimental fibrosis and acute inhibition of JAK2 decreased PP. Thus, JAK2 inhibitors, already in clinical use for other indications, might be a new approach to treat cirrhosis with portal hypertension.